Influence of Personality Type on Employee Work Quality - Ismeilev Kremitz; Jemshid Khobilek (Journal La Bisecoman, 2021)
This study aims to determine the extent of the influence of personality types on the quality of work of employees. The population in this study were employees with a total of 50 people. The sampling method in this study used saturated sampling. The data used in this study are primary and secondary data with data collection methods in the form of observation, questionnaires and literature study. The data analysis technique used is the validity and reliability test, and finally the hypothesis test using the simple linear regression analysis method. Based on the results of data analysis that has been carried out, a simple regression equation model is obtained Y = 17.324 + 0.382 X, which means that personality type has a positive effect on the quality of work of employees and from the results of the t test analysis, a significant value is 0.04 < 0.05 %, which means Personality type affects the quality of work of employees